A full-field optical crazimeter. (25th October 2021) - Kumar, Raj; Varshney, Tushar; Yadav, Tarun; Dwivedi, Gaurav; Barve, S K; Singh, Omendra
Abstract: Quantification of crazing in optical components made of glassy polymers is important as crazing degrades a component's optical performance and mechanical strength. The present work describes a single-beam-based full-field optical crazimeter for imaging and quantification of crazes in transparent samples of plastic using the principles of Fourier optics. A collimated laser beam passes through the sample and acquires information about crazes present in it. A specially designed and fabricated spatial bandpass filter is used in the 4 f optical information processing setup to image crazes present in the sample and reject the noise signal. Digital image processing is used to extract quantitative information about craze density from the recorded images. The proposed crazimeter may enable full-field inspection of consumer products made of various transparent plastics for the presence of crazes.